Vol. 597 : Prospects of Fundamental Sciences Development (PFSD-2019): XVI International Conference of Students and Young Scientists, 23–26 April 2019, Tomsk, Russia; [proceedings]; IOP Conference Series: Materials Science and Engineering - Semenov M. E. Mikhail Evgenievich; Bogdan A. M. Anna Mikhailovna (2019, 2019)
Title screen